2017
DOI: 10.1158/1541-7786.mcr-16-0383
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Downregulation after Anti-EGFR Therapy Predicts the Antitumor Effect in Colorectal Cancer

Abstract: Anti-EGFR mAb is reported to induce EGFR internalization in colorectal cancer cells. However, the biological relevance of EGFR internalization with anti-EGFR mAb is unknown. Therefore, the relevance of EGFR downregulation with anti-EGFR mAb to antitumor activity in colorectal cancer cells was investigated. Quantification of EGFR on the cell surface before cetuximab treatment was assessed by flow cytometry, and its growth-inhibitory effects were measured by Trypan blue exclusion, in 10 wild-type colorectal canc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 37 publications
(39 reference statements)
5
37
0
Order By: Relevance
“…Cetuximab and panitumumab are FDA approved epidermal growth factor receptor (EGFR)‐targeted monoclonal antibodies that have been widely used in treatment of metastatic colorectal cancer (mCRC) after the failure of first‐line chemotherapy; however, a clinical response can be achieved in only 10~20% of unselected patients . Cetuximab and panitumumab mechanisms of action suggest that they function as antagonists of EGFR ligands through the prevention of ligand‐dependent receptor rearrangement, which is essential for inducing its enzymatic activation, as well as promoting receptor degradation and antibody‐dependent cellular cytotoxicity via the triggering of an immune response . Genomic alterations targeting KRAS , NRAS , BRAF , PIK3C A or ERBB2 , loss of PTEN and amplification of EGFR or ERBB2 are now known to be negative predictors associated with the drug efficacy among CRC patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetuximab and panitumumab are FDA approved epidermal growth factor receptor (EGFR)‐targeted monoclonal antibodies that have been widely used in treatment of metastatic colorectal cancer (mCRC) after the failure of first‐line chemotherapy; however, a clinical response can be achieved in only 10~20% of unselected patients . Cetuximab and panitumumab mechanisms of action suggest that they function as antagonists of EGFR ligands through the prevention of ligand‐dependent receptor rearrangement, which is essential for inducing its enzymatic activation, as well as promoting receptor degradation and antibody‐dependent cellular cytotoxicity via the triggering of an immune response . Genomic alterations targeting KRAS , NRAS , BRAF , PIK3C A or ERBB2 , loss of PTEN and amplification of EGFR or ERBB2 are now known to be negative predictors associated with the drug efficacy among CRC patients .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Cetuximab and panitumumab mechanisms of action suggest that they function as antagonists of EGFR ligands through the prevention of ligand-dependent receptor rearrangement, which is essential for inducing its enzymatic activation, [4][5][6] as well as promoting receptor degradation and antibody-dependent cellular cytotoxicity via the triggering of an immune response. 7,8 Genomic alterations targeting KRAS, NRAS, BRAF, PIK3CA or ERBB2, loss of PTEN and amplification of EGFR or ERBB2 are now known to be negative predictors associated with the drug efficacy among CRC patients. [9][10][11][12][13][14][15] To date, biomarker discovery has focused on "negative" biomarkers, those which predict likely failure of EGFR antibody treatment, rather than the identification of "positive" markers which identify patients with specific characteristics where EGFR inhibition may be especially likely to succeed.…”
Section: Introductionmentioning
confidence: 99%
“…5 It has been shown that EGFR is endocytosed upon cetuximab binding and trafficked to late endosomes, leading to lysosomal degradation; in fact, receptor degradation appears to be an important determinant of the antitumor efficacy of cetuximab. 7 We tested whether EGFR undergoes a similar fate after P1X/P2X treatment. Liver organoids from Egfr Em/Em mice were treated with P1X/P2X and then stained with the lysosomal marker LAMP1.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative flow cytometric analysis of EGFR on the cell surface was carried out using mouse antihuman EGFR monoclonal antibody (sc‐120; Santa Cruz Biotechnology, Dallas, TX, USA) and Dako QIFIKIT (Dako, Glostrup, Denmark), as described previously . In brief, cells were incubated with a mouse antihuman EGFR monoclonal antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative flow cytometric analysis of EGFR on the cell surface was carried out using mouse antihuman EGFR monoclonal antibody (sc-120; Santa Cruz Biotechnology, Dallas, TX, USA) and Dako QIFIKIT (Dako, Glostrup, Denmark), as described previously. 22 In brief, cells were incubated with a mouse antihuman EGFR monoclonal antibody. After washing the cells with PBS, The cells were observed by confocal laser microscopy (Nikon A1; Nikon, Tokyo, Japan) and bench top fluorescence microscopy (BIOREVO BZ9000; Keyence, Osaka, Japan).…”
Section: Quantification Of Cell Surface Egfr By Flow Cytometrymentioning
confidence: 99%